PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PADA KERAJINAN PERAK KOTAGEDE - Fitri Naris Wati, Disya; Rizqia Laili, Ina; Maharani, Ari; Anjari, Tiyas; Dwi Budi Astuti , Widya (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
The purpose of this study is to determine the effect of price and product quality on the interest in buying kotagede silver handicrafts. This research uses a quantitative approach with a descriptive method by using the distribution of questionnaires as the main data collection tool. The results of the analysis that have been carried out show that there are 48 respondents with the characteristics of respondents aged 15-27 years more interested in shopping for silverware. This is because people are very concerned about silver handicraft products through price and quality at this age. Based on our research, judging from the results of the multiple linear regression analysis, the value of X1 of 0.506 price variables has a positive and significant effect, meaning that the more the price increases, the more buying interest will increase. The value of X2 of 0.193 product quality variables has a positive and significant effect, meaning that if the product quality increases, it will further increase buying interest.